METAPHORS USED IN BOB DYLAN’S SONGS - Muh. Ma'rifatullah; Murni Mahmud; Abd. Halim (State University of Makassar, 2023)
This study aims to determine the types of metaphors, and the functions of metaphors contained in Bob Dylan's songs. This research is descriptive qualitative research because the purpose of this research is to describe phenomena that occur in terms of language. The data source for this research is Bob Dylan's songs, namely